Regulation Of The Re-Election Of The Village Head From The Perspective Of Legislation - M Fitter Zen; Sukamto Satoto; A Zarkasi (LPPM Universitas PGRI Sumatera Barat, 2024)
The aim of this research is to analyze statutory regulations. which regulates the Village Head Election which is carried out. That in practice, due to disputes in the implementation of the Village Head Election, it is mandatory to carry out a repeat Village Head Election, but it is not regulated in the Legislative Regulations and technical regulations in the implementation of Village Head Elections (Pilkades) in the Batang Hari Regency area. In Law Number 6 of 2014 concerning Villages, hereinafter referred to as Law 6/2014. Then the derivative of Law 6/2014, starting from Government Regulations and Minister of Home Affairs Regulations, does not regulate the re-election of Village Heads in the slightest. In its technical implementation, it is regulated in Batang Hari Regent Regulation Number 32 of 2021 concerning Procedures for Election of Village Heads (hereinafter referred to as Perbup 32/2021). In the technical regulations it is stated that if there is a dispute over the village elections, it will be resolved by the Regent/Mayor. The Regent/Mayor is given the authority to resolve village election disputes that could disrupt democracy in Indonesia. The Regent/Mayor is obliged to resolve the dispute. Village Head Election (Pilkades) dispute resolution is carried out at the settlement stage at the village level, if it is not completed then the settlement stage is at the sub-district level committee, and finally by the district level committee. The failure to resolve the Village Election dispute by the Village Election Committee has forced parties who feel aggrieved to take legal action by filing a lawsuit regarding the Village Election results with the Jambi State Administrative Court. After going through the trial process and arriving at a decision that has permanent legal force (inkracht van gewijsde), the Defendant (Regent) who ratifies and inaugurates the elected Village Head is obliged to carry out re-election.